Prospective feasibility analysis of salvage surgery in recurrent oral cancer in terms of quality of life - Horn, Dominik; Zittel, Sven; Moratin, Julius; Semmelmayer, Karl; Ristow, Oliver; Bodem, Jens; Engel, Michael; Freudlsperger, Christian; Hoffmann, Jürgen; Freier, Kolja (Oral oncology, 2020)
Objectives - The goals of the present study were to prospectively analyze salvage surgery with microvascular reconstruction in recurrent squamous cell carcinoma of the oral cavity (OSCC) in terms of oncological outcome and quality of life. - Patients and methods - From 2012 to 2015, 28 patients underwent salvage surgery due to recurrent OSCC or second primary OSCC without the option of curative re-irradiation. Endpoints were disease-specific survival and progression-free survival after 12 months. The survival was estimated by using the Kaplan-Meier blotting. Quality of life data (European Organization for Research and Treatment of Cancer - EORTC: QLQ-C30 and QLQ-H&N35) was assessed at baseline and subsequently every 3 months up to one year. - Results - Estimated 1-year-survival was 68.4% and progression-free survival was 38.5%. Overall quality of life was significantly reduced three months after salvage surgery [baseline (mean 64.15) versus time 1 (mean 53.04); p = 0.002]. However, the patients experienced a recovery within the first year [baseline (mean 64.15) versus time 4 (mean 70.33); p = 0.176]. Furthermore, the sensation of pain is significantly reduced after salvage surgery [baseline (mean 47.53) versus time 2 (mean 31.25); p = 0.036]. Microvascular reconstruction success rate was 93.1%. - Conclusion - Salvage surgery is a curative treatment option in recurrent and intensively pretreated OSCC. Microvascular reconstruction is feasible with acceptable morbidity and high success rates. Quality of life can be preserved. Further studies combining checkpoint inhibition with salvage surgery are justified.